(3OjhGf GdQGhfOjs - (3GeGe GdOjf aVd Gddg Hf Ydj GdMSfj GdQGhfOj GdbGTGfj,J (B570 (3g` s
(3ChdgG (B:s
(3bGd GdSjO jeOM GdUGMH CHGGdbGSe GdfGUQ Hf Ydj(B: (3MKhG GdeWi agPG GdUHM bO MTQG hUaa GdCab ef CfhGQg WQG s
(3BNQgG (B:s
(3CbHd cGdHOQ aj eOGQYg eTQb aj GdSYO ef eWGdYg Chdg QHY YTQ KGdK hQHY KGfjI LPQ QGHYg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B75s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B108 s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfg edi HWgQGf (B(109) s
Keywords: (3GdCOHs